The Transformation of Adult Higher Education in the Internet Era: Distance Education and Blended Learning Practices - Lintao, Geng (International Conference on Fundamental and Applied Research (I-CFAR), 2026)
In the era of rapid digital transformation, adult higher continuing education has undergone a profound shift, moving from traditional correspondence models to technology-enabled distance and blended learning formats. This study investigates how adult higher education institutions adapt to these changes, with particular attention to the effectiveness, challenges, and international implications of innovative teaching modes. Employing a systematic literature review, the research synthesizes findings from both Chinese and international contexts to identify best practices and persisting gaps. The analysis reveals that blended learning models, combining online modules with face-to-face teaching, enhance flexibility, engagement, and knowledge transfer, but remain limited by uneven digital literacy, insufficient teacher training, and incomplete quality assurance systems. Comparative insights from Europe, the United States, and Southeast Asia highlight the importance of aligning adult education with labor market needs, establishing robust learner support systems, and ensuring equity of access through diversified delivery modes. The study concludes that while blended and online learning are essential for the future of adult higher education, their success depends on policy frameworks, professional development, and context-sensitive innovation. These findings provide practical implications for educators, administrators, and policymakers seeking to optimize adult learning in the digital era.